Rethinking Nature: Phenomenology and a Non-reductionist Cognitive Science. Issue 2 (3rd April 2018) - Gallagher, Shaun
Abstract: Resistance to the idea that phenomenology can be relevant to cognitive scientific explanation has faced two objections advanced, respectively, from both sides of the issue: from the scientific perspective it has been suggested that phenomenology, understood as an account of first-person experience, is ultimately reducible to cognitive neuroscientific explanation; and from a phenomenological perspective it has been argued that phenomenology cannot be naturalized. In this context it makes sense to consider that the notion of scientific reduction is linked to a classic scientific conception of nature. I argue that if properly understood, the proposal to rethink the concept of nature itself, in enactivist phenomenological approaches, undermines the reductionist program and redefines what it means for phenomenology to be naturalized.